2019
DOI: 10.1093/humupd/dmz001
|View full text |Cite
|
Sign up to set email alerts
|

The health of children conceived by ART: ‘the chicken or the egg?’

Abstract: Long-term health Neurodevelopmental health Cardiovascular function and metabolism Growth Respiratory and allergic disorders Malignancies Reproductive health Controlled ovarian stimulation Laboratory factors Culture media Culture time Number of embryos transferred Oocyte donation and gestational surrogacy Oocyte vitrification Epigenetics Imprinting disorders The chicken or the egg? Subfertility and sibling studies Future research Conclusion The conclusion we can reach from the well designed studies aimed at dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
240
3
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(265 citation statements)
references
References 186 publications
(224 reference statements)
11
240
3
11
Order By: Relevance
“…Several studies have own, on the contrary, either better or similar results after ICSI treatment compared with IVF treatment (5,13,(37)(38)(39). As ICSI has mainly been used when male infertility is present, this might be an explanation for the advantage of ICSI, because the women are not necessarily infertile (40).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have own, on the contrary, either better or similar results after ICSI treatment compared with IVF treatment (5,13,(37)(38)(39). As ICSI has mainly been used when male infertility is present, this might be an explanation for the advantage of ICSI, because the women are not necessarily infertile (40).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that even though superovulation produces abnormal oocytes that initiate altered expression of imprinted genes in embryos, compensatory mechanisms regulating imprinted gene networks are able to restore proper levels of gene expression during development. Although, as highlighted across the literature, the alterations in DNA methylation following ART procedures are not always striking and vary between studies (reviewed in Berntsen et al, 2019), in part because of distinctions in treatments used. It was recently reported that human placenta, but not cord blood, from IVF/ICSI showed decreased DNA methylation levels for imprinted loci H19/IGF2 and KCNQ1OT1, as well as for specific repetitive elements (Choux et al, 2018), whereas in another recent study, no obvious overall differences in genome-wide DNA methylation differences in placental tissues were associated with ART (Choufani et al, 2019).…”
Section: Art Proceduresmentioning
confidence: 99%
“…In the past 40 years, more than 7 million babies have been conceived by assisted reproductive technologies (ART) treatment, mainly through in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) (1). Increasing evidence suggests that ART treatment is associated with adverse obstetric and perinatal outcomes, which may be related to the genetic factors of patients, multiple pregnancies and ART procedures per se (1,2). To avoid multiple pregnancies, a single embryo transfer policy has been implemented in many IVF centers.…”
Section: Introductionmentioning
confidence: 99%
“…However, even singletons conceived by ART are also at increased risk of adverse pregnancy outcomes such as low birth weight, preterm birth, small for gestational age, stillbirth, perinatal mortality and gestational diabetes compared with singletons conceived spontaneously (1,2).…”
Section: Introductionmentioning
confidence: 99%